Evaluation of Information Quality Using ISO/IEC 25010:2011 (Case Research: Menu Harianku Application) - Devaldi Akbar Suryadi; Endang Sulistiyani (School of Industrial and System Engineering, Telkom University, 2022)
This research aims to determine the product quality of the Menu Harianku application and recommend improving the quality of the application based on the ISO/IEC 25010:2011 model with 6 characteristics in product quality dimensions namely Functional Suitability, Performance Efficiency, Usability, Reliability, Security, and Portability. ISO/IEC 25010:2011 standard was chosen because of its very suitable characteristics for measuring software quality. Starts with identifying the problem, Design quality, Testing performance quality, and making application improvement recommendations. According to technical characteristics of Functional Suitability, of 97 test cases, there were 11 failed. Performance efficiency of Mobile and Desktop devices scores 86% of the improvement criteria. Reliability Hosting is only accessible in Asian (Japan) and European locations (all) for no more than 20 VUs. Security with Medium-level vulnerabilities. The portability of the application runs well on 6 Desktop & Mobile browsers. According to users the characteristics of Functional Suitability with a percentage of 84.1%, Performance efficiency at 84%, and Usability at 83.5%. As for the application recommendations related to the results of application quality testing that can be used in improving the quality of the Menu Harianku application.